2018
DOI: 10.1038/s41416-018-0298-0
|View full text |Cite|
|
Sign up to set email alerts
|

Direct therapeutic targeting of immune checkpoint PD-1 in pancreatic cancer

Abstract: BackgroundPancreatic cancer (PC) hijacks innate cellular processes to promote cancer growth. We hypothesized that PC exploits PD-1/PD-L1 not only to avoid immune responses, but to directly enhance growth. We also hypothesized that immune checkpoint inhibitors (ICIs) have direct cytotoxicity in PC. We sought to elucidate therapeutic targeting of PD-1/PD-L1.MethodsPD-1 was assessed in PC cells, patient-derived organoids (PDOs), and clinical tissues. Then, PC cells were exposed to PD-L1 to evaluate proliferation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 47 publications
2
37
0
Order By: Relevance
“…Emerging studies have shown that melanoma and breast cancer stem-like cells were enriched for the expression of PD-1 and PD-L1 [12] , respectively. Recent studies have demonstrated that activation of both inhibitory IC ligands and receptors including PD-L1, PD-L2, TIM-3 and PD-1 on the surface of cancer cells promoted various immune-independent hallmarks of cancer such as an altered metabolism, proliferation, invasion and metastasis, DNA repair and chemoresistance [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , and immune checkpoint blockade (ICB) suppressed various hallmarks of cancer including invasion, chemoresistance, proliferation, glycolysis and DNA repair [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies have shown that melanoma and breast cancer stem-like cells were enriched for the expression of PD-1 and PD-L1 [12] , respectively. Recent studies have demonstrated that activation of both inhibitory IC ligands and receptors including PD-L1, PD-L2, TIM-3 and PD-1 on the surface of cancer cells promoted various immune-independent hallmarks of cancer such as an altered metabolism, proliferation, invasion and metastasis, DNA repair and chemoresistance [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , and immune checkpoint blockade (ICB) suppressed various hallmarks of cancer including invasion, chemoresistance, proliferation, glycolysis and DNA repair [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] .…”
Section: Introductionmentioning
confidence: 99%
“…While cell lines are commercially available and can rapidly develop into organoids, they have limitations in their ability to accurately represent characteristics of the primary tumor. Therefore, studies have turned attention to human tissue-derived organoids obtained from surgery or biopsy [6][7][8]. Unlike cell line-derived organoids, patient-derived organoids contain a lumen, multiple cell types, and apicobasal polarity [12].…”
Section: The Role Of Organoid Fibroblasts In Modeling Tumor-stroma Inmentioning
confidence: 99%
“…Organoid culture has gained interest as a valuable in vitro model of molecular interactions and drug sensitivity testing [6]. Organoids are 3D models that have been created from human and murine normal and tumor tissues, and human-derived organoids have been created from biopsy specimens and bulk surgical tissues [6][7][8]. They maintain tumor architecture, genetic profiles, and epigenetic changes of the tissue of origin [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations